Taxonomic study of the genus Evergestis Hübner, 1825 (Lepidoptera: Crambidae: Glaphyriinae) in Iran with description of a new species - Alipanah, Helen; Khodadad, Masoumeh; Rajaei, Hossein; Haseli, Mohammad (Zootaxa, 2018)
The Iranian species of the genus Evergestis were reviewed taxonomically and as a result, Evergestis pazukii sp. n. is described as a new species, E. comealis Amsel stat. n. is raised to species level from the subspecies E. caesialis comealis, and four species, namely E. flavifuscalis Rebel, E. limbata (Linnaeus), E. pechi (Bethune-Baker), and E. serratalis Staudinger are newly reported from Iran. Furthermore, the females of Evergestis africalis (Guenée), and E. nomadalis (Lederer), and the male of E. elbursalis Amsel are described and illustrated for the first time. A redescription of the male of E. hyrcanalis Amsel is provided mainly based on the genital structure, and the male and female genitalia of E. boursini Amsel and E. flavifuscalis Rebel are redescribed, respectively due to their poor descriptions. Additional remarks on the previousely reported species and new data on their distribution in Iran are also provided.